A blockchain based medicine production and distribution framework to prevent medicine counterfeit - Iyolita Islam; Muhammad Nazrul Islam (Journal of King Saud University: Computer and Information Sciences, 2024)
Medicine counterfeiting has raised significant concern in recent years. Falsified and counterfeit drug production and distribution are illegal and a public health concern. The intensity of this problem varies significantly among different countries, depending on how strongly a country’s laws and procedures are followed. Preventing counterfeit medicines has thus become a critical concern, especially in developing and underdeveloped countries. This research aims, firstly, to outline the possible factors of medicine counterfeiting; secondly, to propose a blockchain-based framework to prevent medicine counterfeiting; and thirdly, to evaluate the proposed framework. A content analysis and a semi-structured interview with the key personnel related to the medicine manufacturing and distribution system in Bangladesh were carried out to derive the current scenario of medicine counterfeit. Based on the interviews and content analysis, a set of use cases for preventing medicine counterfeiting in the context of Bangladesh was explored. The required features for developing a digital solution were extracted considering the derived use cases. A blockchain-based framework for preventing medicine counterfeit was proposed by adopting the extracted features. A prototype was developed based on the proposed framework, and an evaluation study was performed to evaluate the prototype. The evaluation study showed that the average block execution time is 201 ms, and the average block time is 482 ms. Again, the proposed framework was found secure, scalable, customer-oriented, and practical compared to other systems.